Social innovation in education: BRAC boat schools in Bangladesh - Jashim Uddin Ahmed; N. M. Ashikuzzaman; Aditi Sonia Mansur Mahmud (Journal of Global Entrepreneurship Research, 2017)
Bangladesh consists of wetlands that pose great threat to the public primary education services. BRAC (Building Resources Across Communities) - a non-governmental organization, therefore, took the opportunity to serve unprivileged children by implementing boat schools model in solving barriers of such uninterrupted education. This case focuses in dealing those threats through the usage of prototype boat schools as a vehicle of social innovation for particular regional development. Thus, BRAC boat schools appear to bring blessings for children in accessing their basic right of education to enlighten the society. The impact of boat schools in education is examined to create positive socio-economic changes. However, this study highlights a brief analysis of the context based on diverse stakeholders and their perspectives to contribute in the theoretical endeavor of social innovation in educational context. It inevitably demands a promising avenue of interests to devise further research on the compatibility of social innovation in education to gear up status of an impoverished society.
Keywords: 650; Bangladesh; BRAC; Social innovation; Primary education; Children; Boat schools